Sistem Pelayanan Dokumen dan Pengaduan Lingkungan Hidup berbasis Web (Studi Kasus : Dinas Lingkungan Hidup Kota Malang) - Dhany Sakti Priabudi; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Environmental Service of Malang City is a government agency engaged in the regional environmental sector which includes activities to supervise, control and control the environment in Malang City. The role of DLH Malang City in providing services requires a permit document for planning activities or business in the environment as legal protection for the environment and society against the impact of issuing administrative decisions. In the environmental document storage process, it is stored in the form of physical documents and electrical documents. In the electrical document storage mechanism, each officer is required to provide data reports on the results of client services related to activities for recapitulation into a computer archive. All data is recapitulated in excel, while environmental document files are stored in the computer directory. The problem that was found was that the review process was not optimal because of the limitations of officers in reporting or client services requiring time and effort to access the archive computer. The complaint mechanism acts as a means of alleged incidental complaints to provide rights and opportunities for the community to be able to take an active role in protecting and managing the environment of Malang City. The problem that was found in this mechanism, DLH Malang city wanted to use the existing website to be able to function as a complaint medium to support the quality of complaint services. Therefore, the authors conducted a study by proposing that this service system was built to help optimize the needs of officers to improve the quality of DLH services in Malang. The waterfall model is used because all needs are clearly defined in advance.